Probing the large Magellanic Cloud's recent chemical enrichment history through its star clusters - Palma, Tali (2015)
We present Washington system colour-magnitude diagrams (CMDs) for 17 practically unstudied star clusters located in the bar as well as in the inner disc and outer regions of the Large Magellanic Cloud (LMC). Cluster sizes were estimated from star counts distributed throughout the entire observed fields. Based on the best fits of theoretical isochrones to the cleaned (C - T1, T1) CMDs, as well as on the δT1 parameter and the standard giant branch method, we derive ages and metallicities for the cluster sample. Four objects are found to be intermediateage clusters (1.8-2.5 Gyr), with [Fe/H] ranging from -0.66 to -0.84. With the exception of SL 263, a very young cluster (~16 Myr), the remaining 12 objects are aged between 0.32 and 0.89 Gyr, with their [Fe/H] values ranging from -0.19 to -0.50. We combined our results with those for other 231 clusters studied in a similar way using the Washington system. The resulting age-metallicity relationship shows a significant dispersion in metallicities, whatever age is considered. Although there seems to exist a clear tendency for the younger clusters to be more metal rich than the intermediate ones, we believe that none of the chemical evolution models currently available in the literature reasonably well represents the recent chemical enrichment processes in the LMC clusters. The present sample of 17 clusters is part of our ongoing project of generating a data base of LMC clusters homogeneously studied using the Washington photometric system and applying the same analysis procedure.